Dictablanda : Politics, Work, and Culture in Mexico, 1938-1968 - Smith, Benjamin T.; Gillingham, Paul, 1973- (Book collections on Project MUSE., 2014)
In 1910 Mexicans rebelled against an imperfect dictatorship; after 1940 they ended up with what some called the perfect dictatorship. A single party ruled Mexico for over seventy years, holding elections and talking about revolution while overseeing one of the world's most inequitable economies. The contributors to this groundbreaking collection revise earlier interpretations, arguing that state power was not based exclusively on hegemony, corporatism, or violence. Force was real, but it was also exercised by the ruled. It went hand-in-hand with consent, produced by resource regulation, political pragmatism, local autonomies and a popular veto. The result was a dictablanda: a soft authoritarian regime.